1999
DOI: 10.1159/000016539
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Apis mellifera Propolis from Two Brazilian Regions on Caries Development in Desalivated Rats

Abstract: The purpose of the present study was to evaluate the effect of Apis mellifera propolis collected from two regions of Brazil on caries development in desalivated rats. Ethanolic extracts of propolis (EEP) were prepared from crude propolis samples collected in Minas Gerais state (MG), southeastern Brazil, and Rio Grande do Sul state (RS), southern Brazil. The flavonoid composition of EEP was analyzed by high–performance thin–layer chromatography (HPTLC) and reversed–phase high–performance liquid chromatography (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0
18

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 31 publications
5
86
0
18
Order By: Relevance
“…10,15,16,23,32 In these studies, ethanolic extracts of propolis, or its bioactive fractions, were applied topically to the molars of rats twice a day for a period of 4 to 5 weeks. Overall, the authors observed anti-caries activity similar to that of Duraphat ® .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,15,16,23,32 In these studies, ethanolic extracts of propolis, or its bioactive fractions, were applied topically to the molars of rats twice a day for a period of 4 to 5 weeks. Overall, the authors observed anti-caries activity similar to that of Duraphat ® .…”
Section: Discussionmentioning
confidence: 99%
“…14 In addition, topical application of the ethanolic extract of other types of propolis was also found to effectively reduce the incidence and severity of carious lesions in vivo. 14,15,16 However, the biological effects of propolis may vary according to the geographical origin and chemical composition of the collected sample. 16 Varnishes are materials widely used in dentistry for the prevention of dental caries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on propolis applications have increased because of its therapeutic and biological properties (5,6). Current research involving propolis in dentistry spans many fields and highlights its antimicrobial and antiinflammatory activities, particularly in cariology, oral surgery, pathology, periodontics and endodontics (5,(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Existem vários relatos atribuindo à própolis as mais variadas aplicações na medicina popular e, de fato, os estudos vêm corroborando que a própolis possui um grande potencial terapêutico, principalmente em relação às atividades antimicrobiana, antiinflamatória, cicatrizante, anestésica, antitripanossomal (GHISALBERTI, 1979;MAREKOV, 1989;KHAYYAL;ELGHAZALY;ELKHATIB, 1993;KUJUMGIEV et al, 1999;MARCUCCI et al, 2001;ALENCAR, 2002;MONTPIED et al, 2003, ALENCAR et al, 2007, anticariogênica (PARK et al 1998a;PARK et al, 1998b;KOO et al, 1999;KOO et al, 2000a;KOO et al, 2000b;ROSALEN et al, 2002;MURATA et al, 2003;DUARTE et al, 2003;HAYACIBARA et al, 2005;CASTRO et al, 2007), antiviral, anticarcinogênica, antioxidante (BURDOCK, 1998MARCUCCI, 1996;CHEN et al, 1996;BANKSOTA et al, 2000;ALENCAR, 2002;CHEN et al, 2003;NAGAI et al, 2003;ASO et al, 2004;ISHIKAWA et al, 2004;NAKAYAMA, 2004;OLDONI, 2007) e fitotóxica (GHISALBERTI, 1979;JOHNSON;EISCHEN;GIANASSI, 1994).…”
Section: Propriedades Biológicas Da Própolisunclassified